Measurement of νμ induced charged current inclusive cross section on water using the near detector of the T2K experiment - Das, Rajarshi, author; Toki, Walter, advisor; Wilson, Robert, committee member; Berger, Bruce, committee member; Menoni, Carmen, committee member (Colorado State University. Libraries, 2016)
The Tokai to Kamioka (T2K) Experiment is a long-baseline neutrino oscillation experiment located in Japan with the primary goal to measure precisely multiple neutrino flavor oscillation parameters. An off-axis muon neutrino beam peaking at 600 MeV is generated at the JPARC facility and directed towards the 50 kiloton Super-Kamiokande (SK) water Cherenkov detector located 295 km away. Measurements from a Near Detector that is 280m downstream of the neutrino beam target are used to constrain uncertainties in the beam flux prediction and neutrino interaction rates. We present a selection of inclusive charged current neutrino interactions on water. We used several sub-detectors in the ND280 complex, including a Pi-Zero detector (P0D) that has alternating planes of plastic scintillator and water bag layers, a time projection chamber (TPC) and fine-grained detector (FGD) to detect and reconstruct muons from neutrino charged current events. We use a statistical subtraction method with the water-in and water-out inclusive selection to extract a flux-averaged, νμ induced, charged current inclusive cross section. We also outline the evaluation of systematic uncertainties. We find an absolute cross section of ⟨σ⟩Φ = (6.37 ± 0.157(stat.) (−1.060/+0.910(sys.)) × 10−39 (cm2/H2O nucleon). This is the first νμ charged current inclusive cross section measurement on water.